Pengaruh Kombinasi Tepung Krokot (Portulaca oleracea L) dan Tepung Daun Kelor (Moringa oleifera L) dalam Ransum terhadap Profil Darah Ayam Kampung Super Fase Grower: Effect of Combination of Purslane Flour (Portulaca oleracea L) and Moringa Leaf Flour (Moringa oleifera L) in Rations on the Blood Profile of Super Village Chicken Grower Phase - Angela Anjelina Timbu; Agustinus Konda Malik; Franky M. S. Telupere (Universitas Nusa Cendana, 2023)
This research was conducted with the aim of studying the effect of a combination of purslane flour (Portulaca oleracea L) combined with Moringa flour (Moringa oleifera L) in rations on the blood profile of super grower stage chickens. The material used was blood samples from 20 chickens. The experiment used a completely randomized block design with 5 treatments and 4 groups. The five treatments studied were P1: commercial feed 90% + 10% purslane + 0% moringa; P2: commercial feed 90% + 7.5% purslane + 2.5% moringa ; P3: commercial feed 90% + 5.0% purslane + 5.0% moringa ; P4: commercial feed 90% + 2.5% purslane + 7.5% moringa ; P5: commercial feed 90% + 0% purslane + 10% moringa. The variables observed were the number of erythrocytes, the number of leukocytes, the hemoglobin level and the hematocrit value. Analysis of variance obtained results showed there was no significant effect (P>0.05) on the research variables. It can be concluded that the combination of purslane flour and moringa leaf meal in the ration with the best combination level was 7.5% purslane flour and 2.5% moringa leaf flour on the blood profile of super-grower stage chickens Riset ini dilakukan dengan maksud mengkaji pengaruh dari kombinasi tepung krokot (Portulaca oleracea L) yang dikombinasikan dengan tepung kelor (Moringa oleifera L) dalam ransum terhadap profil darah ayam kampung super fase grower. Materi yang digunakan adalah sampel darah yang berasal dari 20 ekor ayam. Percobaan menggunakan Rancangan Acak Lengkap Berblok dengan 5 perlakuan serta 4 ulangan. Kelima perlakuan yang diteliti adalah P1: pakan komersial 90% + 10% krokot + 0% kelor; P2: pakan komersial 90% + 7,5% krokot + 2,5% kelor ; P3: pakan komersial 90% + 5,0% krokot + 5,0% kelor ; P4: pakan komersial 90% + 2,5% krokot + 7.5% kelor ; P5: pakan komersial 90% + 0%krokot + 10% kelor. Variabel yang diamati yaitu jumlah eritrosit, jumlah leukosit, kadar hemoglobin dan nilai hematokrit. Analisis ragam mendapatkan hasil berpengaruh tidak signifikan (P>0,05) pada variabel penelitian. Dapat disimpulkan bahwa pemberian kombinasi tepung krokot dan tepung daun kelor dalam ransum dengan level kombinasi terbaik adalah tepung krokot 7,5% dan tepung daun kelor 2,5% tehadap profil darah ayam kampung super fase grower.